Pharmacokinetic study of rational regimen of oral clindamycin in comparison with doxycycline in mild cases of acne vulgaris - Arivazhagan, N.; Kumar, R. Saravana; Kumar, R. Arbind (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Acne vulgaris is a chronic inflammatory disease of pilosebaceous units. It is a common skin disorder affecting both boys and girls in the adolescent age group and also extends into the post adolescent age group. From time immemorial, various remedies have been suggested and followed by Ayurvedic, Siddha, Unani practitioners and native healers present in various parts of the world. In this study an attempt has been made to evaluate the efficacy of a low dose oral Clindamycin in Acne vulgaris and the results of the study have been presented in ensuing chapters. Methods: The Prospective, Randomized Controlled, Single blind study was conducted in Out Patient Section, Department of Dermatology, tertiary care teaching hospital September 2016 to May 2017 for Total six weeks. Drug administration - four weeks. Follow up - two weeks mostly drug used Capsule Clindamycin 50mg. Capsule Doxycycline 100 mg. Benzoyl Peroxide 5% topical cream. Results: The objective of the study is not only to find out the efficacy of a low dose of 50 mg Clindamycin given orally, but also to find out if this efficacy is obtained without producing the adverse effects for which the administration of Clindamycin is hesitated the ant-microbial, Cap. Doxycycline and Cap. Clindamycin act in acne vulgaris by their effect on the Propionibacterium acne. These antibiotics decrease the population of Propionibacterium acne which in turn leads to the inhibition of the bacterial lipases and this is followed by a decrease in concentration of free fatty acids. This produces less tissue inflammation and acne. Conclusions: This study proves the safety and efficacy of low dose of oral Clindamycin in acne vulgaris, and such low doses can also be tried for other infections where the causative organism responds to Clindamycin.